THE VALUE CHAIN OF FISH TECHNIQUES OF FLOATING CAGES AND PONDS IN DEUANYA PROVINCE - & et al., AL- FLUJy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The fish sector is considered an important component of the economies of  many countries in the world  including  Arab countries. It is also considered an important component of  food security. This work is considered as the first attempt to study value chain for fish in Iraq. The objective of this study is to identify the main problems and constrains facing different  links in the  value chain of  fish, and to analyse revenue, production costs, and to calculate some  quantitative indicators  like value added. The results showed that average value added of the  different links is amount to: 22.2dinars/kg , 2012.7 dinar/kg, 109.3 dinar/kg, 872.3 dinars/kg from each links hatcheries, producers, wholesalers and retailers. The results also showed that  the share of different links from value chain for average total value additionrs as follows: 0.73% for  hatcheries link, 66.7% for producer link , 3.6% for wholesalers link, and 28.9%  for retailers link. While cages producers added 65.5% from average value added it is amount to  2912. 7 dinar/ kg; on the level techniques cages floating. The study also identifis the main  challenges and problems facing each link in chain value and forward the suitable solution  and recommendation for government authorities and private sector in order to increase the  efficiency of  fish  in  Iraq.